Small and medium-sized enterprises, business demography and European socio-economic model: Does the paradigm really converge? - Jean Vasile Andrei; Luminita Chivu; Ileana Georgiana Gheorghe; Aleksandar Grubor; Teodor Sedlarski; Violeta Sima; Jonel Subić; Mile Vasic (Journal of Risk and Financial Management, 2021)
Although the European business environment induces important premises and assures conditions in determining economic growth and social well-being, the determinant and existent connections between the evolution of small and medium-sized enterprises (SMEs), business demography characteristics and the European socio-economic model have been scarcely studied in recent years. The dimensions of the European socio-economic model design a very specific framework in developing business demography and assuring a favorable environment for future SME development. The main aim of the manuscript is to investigate the evolution of the European SMEs sector and the perspective of business demography evolution to converge with exigencies of the European socio-economic model. In order to argue the research objective, eight specific and representative business demography variables were employed, from 12 European Union member states (EU-MS), during 2009-2017. Further, the SMEs' performances, determined by changing the economic functional paradigm, were assessed. For proving this, an econometric model was designed considering labor productivity as an endogenous variable. Our preliminary analysis shows considerable differences in business demography indicators and SMEs development among all five socio-economic sub-models of the main European socio-economic model, proving a tight connection between European socio-economic models and SMEs' performance and arguing the necessity of a paradigm convergence. Within some sub-models, there is clear evidence of clustering and convergence in terms of business demography and SMEs future development.
Keywords: 330; business model; business demography; economic behavior; economic performance; employment; productivity; SME's